2017
DOI: 10.1111/ijlh.12726
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the lymphocyte positional parameters in the Sysmex XN haematology analyser in lymphoproliferative disorders and mononucleosis syndrome

Abstract: The lymphocyte positional parameters provided by Sysmex XN analysers are useful to differentiate expansions of T-GLs from other LPD and to differentiate MNS cases from other diagnostic groups. In addition, these parameters are very useful for detecting changes in the lymphocytes that make it necessary to review blood smears in samples without morphological flagging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…These represent numerical values correlated to the intrinsic biophysical properties and morphology of leukocytes. UniCel DxH 800 haematology analyser measures positional parameter with VCS technology (Volume, Conductivity, and Scatter), using 3 independent energy sources simultaneously: direct current impedance to measure cell volume of all cell types; radio frequency opacity, to characterize conductivity for internal composition of each cell; a laser beam to measure light scatter for cytoplasmic granularity and nuclear structure [ 20 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…These represent numerical values correlated to the intrinsic biophysical properties and morphology of leukocytes. UniCel DxH 800 haematology analyser measures positional parameter with VCS technology (Volume, Conductivity, and Scatter), using 3 independent energy sources simultaneously: direct current impedance to measure cell volume of all cell types; radio frequency opacity, to characterize conductivity for internal composition of each cell; a laser beam to measure light scatter for cytoplasmic granularity and nuclear structure [ 20 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Since most individual CBC or VCS parameters were not powerfully discriminatory between the two groups, combinatorial approaches were used to construct LIS-compatible logistic regression equations/models with binary outcomes i.e. 0 or 1 corresponding to benign or clonal etiologies [12]. Different strategies were adopted to obtain these models-forward, backward and manual stepwise regression procedures.…”
Section: Discussionmentioning
confidence: 99%
“…overfitting), we focused on the percentage of correctly classified cases rather than ROC curves in selecting best models. The models' optimal cut-offs were derived using receiver operating characteristics (ROC) curves [12].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that NE CPD parameters (i.e., NE-SSC, NE-SFL) may be useful for diagnosing myelodysplastic syndromes and sepsis, whilst NE-SFL and MO-WX may play a role in differential diagnosis of some acute leukemias (4, 5, 6, 7, 8, 9). Some LY CPD parameters (i.e., LY-X, LY-Y and LY-Z) may then provide valuable information for screening lymphoproliferative diseases (10, 11). Nevertheless, little information is available on the analytical quality specification of CPD, and even less is known on the degree of harmonization of these measures among different instrumentation and clinical laboratories.…”
Section: Introductionmentioning
confidence: 99%